136k views
1 vote

(xdx)/((x^(2)+4)^(3) )

User Lyle Z
by
4.1k points

1 Answer

4 votes

Substitute
u=x^2+4 and
du=2x\,dx. Then the integral transforms to


\displaystyle \int (x\,dx)/((x^2+4)^3) = \frac12 \int (du)/(u^3)

Apply the power rule.


\displaystyle \int (du)/(u^3) = -\frac1{2u^2} + C

Now put the result back in terms of
x.


\displaystyle \int (x\,dx)/((x^2+4)^3) = \frac12 \left(-\frac1{2u^2} + C\right) = -\frac1{4u^2} + C = \boxed{-\frac1{4(x^2+4)^2} + C}

User Yuit
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.